TaSPL17s act redundantly with TaSPL14s to control spike development and their elite haplotypes may improve wheat grain yield - Chen, Hao; Zhang, Xing; Xu, Shuhao; Song, Chengxiang; Mao, Hailiang (Frontiers in Plant Science, 2023)
Wheat is a staple crop for the world's population, and there is constant pressure to improve grain yield, which is largely determined by plant architecture. SQUAMOSA PROMOTER-BINGDING PROTEIN-LIKE (SPL) genes have been widely studied in rice, including effects on plant architecture, grain development, and grain yield.However, the function of SPL homologous genes in wheat has not been well investigated. In this study, TaSPL14s and TaSPL17s, wheat's closest orthologous of OsSPL14, were functionally investigated using gene-editing assays, revealing that these genes redundantly influence plant height, tiller number, spike length, and thousandgrain weight (TGW). Bract outgrowth was frequently observed in the hexa-mutant, occasionally in the quintuple mutant but never in the wild type. Transcriptome analysis revealed that the expression of plenty of spike development associated genes were altered in taspl14taspl17 hexa-mutants compared to that in wild type. In addition, we analyzed the sequence polymorphisms of TaSPL14s and TaSPL17s among wheat germplasm and found superior haplotypes of TaSPL17-A and TaSPL17-D with significantly higher TGW, which had been positively selected during wheat breeding.Accordingly, dCAPS and KASP markers were developed for TaSPL17-A and TaSPL17-D, respectively, providing a novel insight for molecular marker-assisted breeding in wheat. Overall, our results highlight the role of TaSPLs in regulating plant architecture and their potential application for wheat grain yield improvement through molecular breeding.